2021
DOI: 10.1093/eurjpc/zwab224
|View full text |Cite
|
Sign up to set email alerts
|

Major adverse cardiovascular events in homozygous familial hypercholesterolaemia: a systematic review and meta-analysis

Abstract: Aims Homozygous familial hypercholesterolaemia (HoFH) is a genetic condition characterized by extremely elevated levels of low-density lipoprotein cholesterol and premature atherosclerotic cardiovascular disease and death. Due to its rarity, accurate assessment of cardiovascular outcomes associated with HoFH and how they have changed over time has been challenging. The goal of this study was to assess the prevalence and age-of-onset of major adverse cardiovascular events (MACE) among patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…The safety and efficacy of inclisiran were also assessed in patients with homozygous familial hypercholesterolemia (HoFH) in the ORION-5 study [ 95 , 96 ]. The disease, as a consequence of mutations in LDLR , APOB , or PCSK9 genes inherited from both parents, is characterized by extremely elevated LDL-C levels and, subsequently, high risk for premature cardiovascular diseases [ 97 , 98 ]. Participants who met the inclusion criteria were randomly assigned to receive either a dose of 300 milligrams of inclisiran or a placebo.…”
Section: Inclisiran—a Novel Pcsk9 Inhibitormentioning
confidence: 99%
“…The safety and efficacy of inclisiran were also assessed in patients with homozygous familial hypercholesterolemia (HoFH) in the ORION-5 study [ 95 , 96 ]. The disease, as a consequence of mutations in LDLR , APOB , or PCSK9 genes inherited from both parents, is characterized by extremely elevated LDL-C levels and, subsequently, high risk for premature cardiovascular diseases [ 97 , 98 ]. Participants who met the inclusion criteria were randomly assigned to receive either a dose of 300 milligrams of inclisiran or a placebo.…”
Section: Inclisiran—a Novel Pcsk9 Inhibitormentioning
confidence: 99%
“…However, the effect of all these conventional agents is not sufficient to achieve adequate LDL-C reduction, and more effective add-on LLTs are required in most cases. Moreover, a recent meta-analysis of 94 studies conducted on HoFH patients showed that the age-onset of major adverse cardiovascular events has been delayed 11 years in the post-1990 compared to the pre-1990 era, but the prevalence of ASCVD has not changed, emphasizing the need for new treatment approaches on top of conventional LLT [ 17 ].…”
Section: Conventional Lipid Lowering Therapymentioning
confidence: 99%
“…Variants in 3 of the causal genes— LDLR , APOB , and PCSK9 —display autosomal semidominant inheritance, while variants in the LDLRAP1 gene underlie a rare recessive form of HoFH . The cumulative LDL-C burden is substantial from birth onwards, giving rise to a very high risk of premature atherosclerotic cardiovascular disease (ASCVD) . Patients with HoFH may already experience an ASCVD event before reaching adulthood or before the condition is diagnosed and treatment can be initiated .…”
Section: Introductionmentioning
confidence: 99%